Странствия мага: [роман] / иллюстрации Лео Хао - Перумов Николай Данилович (2002)
Экземпляры: ФИЛ (20210201) / Инвентарный номер: 1112781 / Цена: / Сис.шифр: 84(2) / Авт.знак: П 27 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-4